qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = - \left ( x + 1 \right )$
$y = 13 + x$
$x$Intercept
$\left ( - 1 , 0 \right )$
$y$Intercept
$\left ( 0 , - 1 \right )$
$x$Intercept
$\left ( - 13 , 0 \right )$
$y$Intercept
$\left ( 0 , 13 \right )$
$- \left( x+1 \right) = 13+x$
$x = - 7$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ - } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 13 + x$
$ $ Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses $ $
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = 13 + x$
$- x - 1 = \color{#FF6800}{ 13 } \color{#FF6800}{ + } \color{#FF6800}{ x }$
$ $ Organize the expression $ $
$- x - 1 = \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 13 }$
$- x - 1 = \color{#FF6800}{ x } + 13$
$ $ Move the variable to the left-hand side and change the symbol $ $
$- x - 1 \color{#FF6800}{ - } \color{#FF6800}{ x } = 13$
$- x \color{#FF6800}{ - } \color{#FF6800}{ 1 } - x = 13$
$ $ Move the constant to the right side and change the sign $ $
$- x - x = 13 \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } = 13 + 1$
$ $ Organize the expression $ $
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = 13 + 1$
$- 2 x = \color{#FF6800}{ 13 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$ $ Add $ 13 $ and $ 1$
$- 2 x = \color{#FF6800}{ 14 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 14 }$
$ $ Change the sign of both sides of the equation $ $
$2 x = - 14$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 14 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
$x = - 7$
Solve the fractional equation
$\color{#FF6800}{ - } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 13 } \color{#FF6800}{ + } \color{#FF6800}{ x }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
Solution search results
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo